2019
DOI: 10.1093/jxb/erz353
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress increases the use of cytosolic pyruvate for isoprene biosynthesis

Abstract: The increasing occurrence of heatwaves has intensified temperature stress on terrestrial vegetation. Here, we investigate how two contrasting isoprene-emitting tropical species, Ficus benjamina and Pachira aquatica, cope with heat stress and assess the role of internal plant carbon sources for isoprene biosynthesis in relation to thermotolerance. To our knowledge, this is the first study to report isoprene emissions from P. aquatica. We exposed plants to two levels of heat stress and determined the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 92 publications
6
21
1
2
Order By: Relevance
“…(2018) proposed that depending on the availability photochemical energy supply and the limitations imposed by either Rubisco activity or RuBP regeneration (under high and low CO 2 and temperature) multiple alternative carbon sources can fuel the MEP pathway. They conclude that the use of alternative carbon sources is greater under photosynthesis-limiting conditions, which is in line with our results, showing that the use of cytosolic pyruvate for de novo synthesis is strongly enhanced under heat stress and limited photosynthetic carbon fixation ( Yáñez-Serrano et al, 2019 ) ( Figure 4 ). However, there could also be alternative pathways which are currently not understood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(2018) proposed that depending on the availability photochemical energy supply and the limitations imposed by either Rubisco activity or RuBP regeneration (under high and low CO 2 and temperature) multiple alternative carbon sources can fuel the MEP pathway. They conclude that the use of alternative carbon sources is greater under photosynthesis-limiting conditions, which is in line with our results, showing that the use of cytosolic pyruvate for de novo synthesis is strongly enhanced under heat stress and limited photosynthetic carbon fixation ( Yáñez-Serrano et al, 2019 ) ( Figure 4 ). However, there could also be alternative pathways which are currently not understood.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, 13 CO 2 decarboxylation was significantly higher from 13 C1-pyruvate than from 13 C2-pyruvate ( Figure 5), and thus cells were exposed to higher 13 CO 2 concentrations from 13 C1-pyruvate decarboxylation. Therefore, the impact of refixation would be expected to be higher from 13 C1-pyruvate feeding, which was clearly not the case (Yáñez-Serrano et al, 2019) (Figure 4). It has recently been shown that there is substantial elasticity in the MEP pathway, strongly related to the availability of reducing power and ATP from photochemical reactions (Rasulov et al, 2015;Rasulov et al, 2018).…”
Section: Dynamic Response Of Terpenoid Emissions To Heat Stressmentioning
confidence: 93%
“…Similar results were shown with drought stress in poplar [44]. This variability in the degree of incomplete labeling has been considered to reflect carbon sources for the MEP pathway other than the CBC, especially pyruvate used by the MEP pathway [40,42,[45][46][47]. However, it is unknown if CBC metabolites follow the same labeling pattern under these conditions.…”
Section: Introductionsupporting
confidence: 65%
“…It has been shown that PGA and isoprene remain partially unlabeled when fed 13 CO 2 or 14 CO 2 [5][6][7][38][39][40]63,64]. Although the first report of incomplete labeling of isoprene pointed out the connection between incomplete labeling of the CBC and isoprene [38], most reports of isoprene labeling have interpreted incomplete labeling in isoprene as an indication of carbon sources other than the CBC, often proposing an alternative source for pyruvate, typically by glycolysis of old carbon [42,45]. In other words, label in isoprene was the result of fully labeled GAP and a variable amount of unlabeled pyruvate.…”
Section: Lack Of Complete Labeling Of the Cbc And Isoprenementioning
confidence: 99%
“…When alternate possibilities exist to synthesize a molecule, the relative amount of 13 C from different positions found in product molecules can be used to determine the relative importance of each possible synthesis pathway. Position‐specific 13 C labeling has been successfully employed to track the flow of glucose and pyruvate into smaller isoprenoids, including isoprene, monoterpenes, sesquiterpenes and diterpenes, illuminating their fluxes and production pathways (Ghirado et al ., 2014; Jardine et al ., 2014; Fasbender et al ., 2018; Yáñez‐Serrano et al ., 2018, 2019; Werner et al ., 2020). Although it has similar promise to resolve the amount of interchange of molecular precursors between the MVA and MEP pathways for larger isoprenoids such as sterols, position‐specific 13 C labeling has not yet been used for that purpose.…”
Section: Introductionmentioning
confidence: 99%